Degradasi Lingkungan Terhadap Pertumbuhan Ekonomi di 5 Provinsi Pulau Jawa Tahun 2012-2021 - Iis Sugiarti; Ika Nur Safitri; Desty Hapsari; Dinar Melani Hutajulu (Universitas 45 Surabaya, 2025)
Java Island has become the region that contributes the highest GDP in Indonesia. However, the problem of environmental quality degradation that has occurred on the island of Java for decades is still a dilemma. The aim of this study is to analyze the influence of environmental degradation variables on economic growth on the island of Java. This study took five provinces on the island of Java, namely DKI Jakarta, West Java, Central Java, DI Yogyakarta, and East Java in 2012-2021. The use of secondary data in this study comes from the Statistics Indonesia. Data analysis uses panel data regression. The findings from this study include CO2 emissions which are positively related, but not significant, to GRDP per capita. Population density is positively and significantly related to GRDP per capita. Likewise, the use of electricity consumption is positively and significantly related to GRDP per capita as a derivative of economic growth.